Malaria case clinical profiles and Plasmodiumfalciparum parasite genetic diversity: a cross sectional survey at two sites of different malaria transmission intensities in Rwanda. (December 2016) - Kateera, Fredrick; Nsobya, Sam; Tukwasibwe, Stephen; Mens, Petra; Hakizimana, Emmanuel; Grobusch, Martin; Mutesa, Leon; Kumar, Nirbhay; Vugt, Michele
Abstract Background Malaria remains a public health challenge in sub-Saharan Africa withPlasmodium falciparum being the principal cause of malaria disease morbidity and mortality.Plasmodium falciparum virulence is attributed, in part, to its population-level genetic diversity—a characteristic that has yet to be studied in Rwanda. CharacterizingP. falciparum molecular epidemiology in an area is needed for a better understand of malaria transmission and to inform choice of malaria control strategies. Methods In this health-facility based survey, malaria case clinical profiles and parasite densities as well as parasite genetic diversity were compared amongP. falciparum -infected patients identified at two sites of different malaria transmission intensities in Rwanda. Data on demographics and clinical features and finger-prick blood samples for microscopy and parasite genotyping were collected. Nested PCR was used to genotypemsp -2 alleles of FC27 and 3D7. Results Patients' variables of age group, sex, fever (both by patient report and by measured tympanic temperatures), parasite density, and bed net use were found differentially distributed between the higher endemic (Ruhuha) and lower endemic (Mubuga) sites. Overall multiplicity ofP. falciparum infection (MOI) was 1.73 but with mean MOI found to vary significantly between 2.13 at Ruhuha and 1.29 at Mubuga (p < 0.0001). At Ruhuha, expected heterozygosity (EH ) for FC27 and 3D7 alleles were 0.62 and 0.49, respectively, whilst at Mubuga, EH for FC27 and 3D7 were 0.26 and 0.28, respectively. Conclusions In this study, a higher geometrical mean parasite counts, more polyclonal infections, higher MOI, and higher allelic frequency were observed at the higher malaria-endemic (Ruhuha) compared to the lower malaria-endemic (Mubuga) area. These differences in malaria risk and MOI should be considered when choosing setting-specific malaria control strategies, assessing p. falciparum associated parameters such as drug resistance, immunity and impact of used interventions, and in proper interpretation of malaria vaccine studies.